2012
DOI: 10.1186/1477-7525-10-84
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic growth, depressive symptoms, posttraumatic stress symptoms, post-migration stressors and quality of life in multi-traumatized psychiatric outpatients with a refugee background in Norway

Abstract: BackgroundPsychiatric outpatients with a refugee background have often been exposed to a variety of potentially traumatizing events, with numerous negative consequences for their mental health and quality of life. However, some patients also report positive personal changes, posttraumatic growth, related to these potentially traumatic events. This study describes posttraumatic growth, posttraumatic stress symptoms, depressive symptoms, post-migration stressors, and their association with quality of life in an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
151
2
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(162 citation statements)
references
References 138 publications
(190 reference statements)
5
151
2
4
Order By: Relevance
“…Posttraumatic growth significantly predicted QOL in a manner that people who displayed more personal growth reported higher QOL. These findings are consistent with the results of previous studies where PTSD and posttraumatic growth showed significant direct and/or indirect effect on quality of life perceptions (Schnurr et al 2006, Teodorescu et al 2012) and the effects are both indirect and direct (Kashdan & Kane 2011).…”
Section: Discussionsupporting
confidence: 83%
“…Posttraumatic growth significantly predicted QOL in a manner that people who displayed more personal growth reported higher QOL. These findings are consistent with the results of previous studies where PTSD and posttraumatic growth showed significant direct and/or indirect effect on quality of life perceptions (Schnurr et al 2006, Teodorescu et al 2012) and the effects are both indirect and direct (Kashdan & Kane 2011).…”
Section: Discussionsupporting
confidence: 83%
“…In this study it was observed that there is a significant correlation between satisfaction and importance of the quality of life dimensions and posttraumatic growth that this finding is in line with the results of the study of Halam (2012) and Thoedoresco et al (2012), where it was determined there is a direct and significant correlation between posttraumatic growth and quality of life [15][16] . Also, Tomich and Helgeson (2006) in their research stated that individuals whose mental dimension of their quality of life is lower, experience higher growth 17 .…”
Section: Discussionsupporting
confidence: 81%
“…An anxiety score of > 1.75 represents a clinical level of anxiety that was found to be consistent with several anxiety diagnoses, whereas a depression score > 1.75 represents a clinical level of depression found to be consistent with major depressive disorder (Mollica et al, 2004). In studies of traumatized refugee populations of various ethnic backgrounds, internal consistency for the HSCLÀ25 has been reported with Cronbach's alpha ranging from .83 to .96 (e.g., Bentley et al, 2012;Renner, Salem, & Ottomeyer, 2006;Teodorescu et al, 2012). We obtained a Cronbach's alpha for the HSCLÀ25 of .91 at T1, .94 at T2, and .94 at T3.…”
Section: The Hopkins Symptom Checklistà25mentioning
confidence: 69%
“…The WHOQOLÀBREF has frequently been used in research of traumatized populations, often in conjunction with the HTQ and the HSCLÀ25 (e.g., Teodorescu et al, 2012). Scoring is marked on 5-point Likert scales ranging from 1 (very dissatisfied) to 5 (very satisfied), disagree strongly to agree strongly, and related formulations.…”
Section: The World Health Organization Quality Of Lifeàbrefmentioning
confidence: 99%